Socio-Cultural Factors Affected Women of Childbearing Age Using Intrauterine Devices (IUDs) - Puspa Sari; Juda Julia Kristiarin; Blacius Dedi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Intrauterine devices (IUDs) use in Indonesia remains low (7.4%) compared to other contraceptive methods. In Langkat Regency, IUD coverage is only 5.2% of the total number of women with reproductive health problems (PUS), a decrease from the previous year (6.1%). Various socio-demographic, economic, socio-cultural, and health factors, and the role of health workers, are thought to influence women's decisions to use IUDs. The purpose of this study was to determine the influence of culture on the use of Intrauterine Device contraception in women of childbearing age. Method: An observational, analytical, quantitative survey with a cross-sectional design involving 296 women of childbearing age at Pangkalan Brandan Community Health Center (n=184) and Tangkahan Durian Community Health Center (n=112). The sample was selected using purposive sampling with inclusion criteria of women aged 15-49 years who are active family planning users. Data were collected using a structured questionnaire, the validity and reliability of the questionnaire were found to be very good (>0.75), The internal consistency reliability of this study was obtained with a Cronbach's coefficient of 0.938, and analyzed using the Chi-Square test to assess the relationship between variables. The results of the Chi-Square test of social norms with the use of IUD contraception, namely p=0.000, showed a significant relationship. Social norms are associated with the use of IUS contraception in women of childbearing age. A comprehensive education program, improved counseling quality, and strengthened social support are needed to increase IUD coverage in Langkat Regency.